Teknologi Location Based Service (Global Positioning System) Pada Perangkat Mobile - Yulianto, Budi (ComTech: Computer, Mathematics and Engineering Applications, 2010)
Article presents analysis and design of software using Location Based Service (LBS) that is part of communication technology based on geographic position. The goal of the research is designing LBS application to be implemented on mobile device that has GPS (Global Positioning System) technology and uses GPRS (General Packet Radio Service) to connect to server for generating shortest path by Dijkstra algorithm method Fibonacci Heap. Software development method used is LBS application implemented on mobile device. Conclusion of the research has shown that shortest path generated using Dijkstra algorithm method Fibonacci Heap as single source shortest path is faster than Dijkstra algorithm and Bellman Ford.